TECHNICAL TRAINING ON THE DEVELOPMENT AND MAINTENANCE OF DATA LIBRARY AND MAPROOMS - Diarra, Afoussatou (2024)
This report documents the technical training workshop on the development and maintenance of Data Libraries and Maprooms, conducted from August 8 to 14, 2024, at the Nigerian Meteorological Agency (NiMet) in Abuja. Organized as part of the AICCRA-MALI project, the workshop aimed to enhance the capacity of MALI-METEO staff to develop, maintain, and utilize climate data platforms effectively.